Faunistic and diagnostic notes on some species of the genus Omalium Gravenhorst, 1802 of Caucasus, Turkey and Iran (Coleoptera: Staphylinidae: Omaliinae, Omaliini) - Shavrin, Alexey V.; Khachikov, Eduard A. (Zootaxa, 2023)
Faunistic and diagnostic notes on eleven species of the genus Omalium Gravenhorst, 1802 of Caucasus, Turkey and Iran are presented. Faunistic data of all species are summarized, and distributional maps for O. falsum Eppelsheim, 1889, O. turcicum Smetana, 1967 and O. wunderlei Zanetti, 2002 are given. Several new records are provided for the first time from certain areas: O. caesum Gravenhorst, 1806 from several regions of Russia (Stavropol Territory, Karachay-Cherkessia, North Ossetia-Alania) and Armenia, O. falsum from Russia and Iran, O. excavatum Stephens, 1834 from Krasnodar Territory and Karachay-Cherkessia, O. littorale Kraatz, 1857 from Kabardino-Balkaria and Dagestan, O. rivulare (Paykull, 1789) from Kabardino-Balkaria and Iran, O. rugatum Mulsant & Rey, 1880 from south-western region of Russia, Georgia and Iran, and O. turcicum from Russia.